Acknowledgements - Jade Lee (Janeway JS, 2018)
Acknowledgements for the second issue of Brief Encounters.
Keywords: Climate Change; Science Fiction; speculative fiction; futurism; energy crisis; sustainable and unsustainable energy resources; art; science